Implementasi Pembelajaran Berbasis Nilai-Nilai Islami Dalam Meningkatkan Mutu Pendidikan Agama di MTsN 1 Palembang - Titi Oktarina Sambadha; Ranita Ranita; Saipul Annur; Asri Karolina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to describe and analyze the implementation of Islamic values-based learning in improving the quality of religious education at MTsN 1 Palembang, as well as to identify the supporting factors, inhibiting factors, and its impact on the quality of students' religious education. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation study involving the principal, teachers, and students. Data analysis was conducted using the interactive model developed by Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing with verification. The findings indicate that MTsN 1 Palembang has systematically implemented Islamic values-based learning through the integration of religious values into the curriculum, instructional methods, school culture, and teachers' exemplary roles. The impact of this implementation proved significant in improving the quality of religious education, as reflected in the enhancement of students' religious understanding, improvement of their moral attitudes and behavior, and the development of their practical religious skills.